Neumografía por impedancia como alternativa para la valoración de la apnea obstructiva del sueño - Olmos, D.; Rodríguez, J. L.; Gaitán, M. J.; Pimentel, A. B. (Revista Mexicana de Ingenieria Biomedica, 2007)
The evaluation of the obstructive sleep apnea is commonly done by polysomnography. During this disease, the respiratory signals can be observed as respiratory efforts (thoracic/abdominal movements) without airflow and a consequent oxygen saturation reduction. The technique used to define the respiratory signal by the Instituto Nacional de Enfermedades Respiratorias is the inductance plethysmography. However, in Mexico, there is a technology availability trouble for the absence of a technology provider of the instrument itself, transducers or service. In this work, an evaluation of two other technological technologies is presented, the impedance pneumography and the displacement respirometry. For the primer, a cost evaluation was also done. Using a Fleish pneumotachometer as a reference signal, the volume and frequency obtained by these two techniques showed that the impedance pneumography presented high correlations and it was capable of following the respiratory movements in obstructive sleep apnea simulations. Although the cost evaluation resulted in slightly higher costs than the inductance technique, the qualitative costs of using impedance pneumography suggest benefits for the technological substitution.